REVIEW OF INDONESIAN CONSTITUTIONAL COURT DECISION NUMBER 135/PHP.BUP-XIX/2021 - Putri Aprilia Anggraini; Anna Erliyana (Universitas Internasional Batam, 2022)
The determination of the elected Regent and Deputy Regent by the General Election Commission (KPU) of Sabu Raijua Regency was formed without paying attention to the provisions of the Legislation and General Principles of Good Governance. The reason is that Orient Riwu Kore was only known to have dual citizenship after issuing the KPU Decree. The Constitutional Court later annulled the KPU decree. In contrast, Article 24C of the Constitution mandates that the MK's authority decide disputes regarding the general election results. On the other hand, the KPU stipulation decree is related to the general election process, not a dispute over the vote results. The dispute resolution process should be done through administrative efforts to the BAWASLU and the PTUN. Therefore, it becomes a question regarding the basis of the authority and reasons for the Constitutional Court to resolve disputes over the general election process. This research is in the form of normative juridical. The approach used in this research is the statutory approach and the case approach. This research is categorized in a prescriptive research typology. The data that has been collected will be analyzed qualitatively, and the results of this study are categorized in the form of prescriptive-analytical research. The result of this research show if the dispute of the KPU decree should be solved by administrative efforts in the form of adjudication to Bawaslu. Only then can the PTUN lawsuit be filed. However, suppose the dispute resolution process is carried out through the Administrative Court, it will take a long time. So that it can be understood that the acceptance of the applicant's application by the Constitutional Court is due to the absence of a more effective mechanism that can be carried out for the determination of the KPU decree other than through the Constitutional Court. Keywords: election disputes; constitutional court decision; decrees; general election commissions.